A new species of Odontites (Orobanchaceae) from southern Italy - Brullo, Salvatore; Tomaselli, Valeria; Wagensommer, Robert Philipp (Phytotaxa, 2015)
Odontites sillettii, a new species from central Apulia (Southern Italy), is described and illustrated. This species is morphologically closely related to O. rigidifolius, endemic to Sicily, from which it differs in several features regarding leaves, calyx, corolla, anthers and pistil. The seed testa and pollen micromorphology, ecology, conservation status and its relationships with the hitherto known species of Odontites are examined, as well as an analytical key of the annual species of Odontites characterized by glabrous corolla on the abaxial face is provided.